2002
DOI: 10.1002/1521-3773(20021004)41:19<3683::aid-anie3683>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

(C2H10N2)[Cr(HPO3)F3]: The First Organically Templated Fluorochromium(III) Phosphite

Abstract: In recent years the search for new open-framework materials with transition metal elements has become the focus of much interest due to the potential application of these materials as absorbents, ion exchangers, solid-state electrolytes, and catalysts in heterogeneous catalysis. [1] Such applications are not possible with main group systems of tetrahedral framework zeolites. The syntheses of these materials usually involve organic templates, for example organic diamines, for generating large cavities and are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 5 publications
2
43
0
Order By: Relevance
“…In recent years, much effort has devoted to preparing metal phosphates with novel structures and interesting topologies [2][3][4][5][6][7]. However, the generation of such phosphates with large openframework structures still remains a great challenge because of the high coordination tendency and flexibility of PO 4 group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, much effort has devoted to preparing metal phosphates with novel structures and interesting topologies [2][3][4][5][6][7]. However, the generation of such phosphates with large openframework structures still remains a great challenge because of the high coordination tendency and flexibility of PO 4 group.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that binuclear zinc units, HPO 3 molecules directed into the channels, which is rare reported in metal phosphates/phosphite (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…And most "oxo-anion part" work has been carried out on the [PO 4 ] 3− anion [1][2][3][4][5]. In addition to phosphates, open framework metal arsenates [6,7], phosphites [8][9][10], selenites [11,12], germinates [13,14] and carbonates [15] have been reported in the literature. Recently, there has been growing interest in the study of open-framework architectures containing oxo-anions of sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…has attracted considerable attention [10][11][12][13]. Harrison et al [14] reported the first organically templated zincophosphite.…”
Section: Introductionmentioning
confidence: 99%